Enablers for integrated operations diagnosis and improvement - Ramly, Edly Ferdin; Mohammad, Musli; Yahya, Mohd Shahir (Asian Research Publishing Network (ARPN), 2016)
In order for organizations to improve their performance, they shall identify their operations opportunities for improvement. The process to identify the opportunities for improvement is referred herein as “diagnosis” process. The most common systematic operations diagnosis and improvement approaches are Quality Audit, Organizational Assessment based on Business Excellence Framework and Project Selection for Lean and Six Sigma. All these three approaches should be integrated in order to grasp the fruitful benefits for the organizations. The benefits include; minimize redundancies, improve the operations performance and eventually assist in achieving certification and award. This paper proposes the enablers for operations diagnosis and improvement based on integration of ISO19011 Quality Audit framework, Business Excellence Framework and Lean Six Sigma approaches.